Coloring Play Therapy on Hospitalization Anxiety Levels in Preschool-Aged Children - Palesa, Hayati; Fauzan, Fauzan; Mariani, Andi; Fahrurezi, Fahrurezi (Sarana Ilmu Indonesia (salnesia), 2025)
Hospitalization can trigger a range of reactions, from mild to severe, that interfere with a child's care and potentially impede the recovery process. The prevalence of anxiety in children reaches 60-80% of the general population during hospitalization, thus requiring special attention from caregivers. This study aimed to identify the effect of coloring picture play therapy on the anxiety levels of preschool children during their stay at Madani Regional General Hospital, Palu. This quantitative study employed a pre-experimental method with a single-group pre-test-post-test design. The population consisted of 337 children hospitalized over the last three months. A sample of 53 participants who met the inclusion criteria was selected using cluster random sampling. Data on anxiety levels were collected before and after the coloring picture play therapy and were analyzed using Wilcoxon Signed-Rank Test at a significance level of p<0,05. The results showed that before the therapy, one child (1,9%) had mild anxiety, 10(18,9%) had moderate anxiety, 39(73,6%) had severe anxiety, and 3(5,7%) experienced panic. After the therapy, no subjects were found to have severe anxiety or panic; anxiety levels shifted to moderate for 32,1% and mild for 67,9% of the children. Based on the findings, which indicate a significant decrease in anxiety (p<0,05), it is concluded that coloring picture play therapy is effective in reducing hospitalization-induced anxiety in preschool children.